PENGARUH KOMPETENSI, ETOS KERJA DAN DUKUNGAN ORGANISASI TERHADAP KINERJA PEGAWAI SERTA DAMPAKNYA TERHADAP KINERJA KANTOR KESYAHBANDARAN DAN OTORITAS PELABUHAN MALAHAYATI - Muhammad Muslim; Said Musnadi; Teuku Meldi Kesuma (Jurnal Magister Manajemen, 2018)
The purpose of this research is to know:  (1) the state of competence, work ethic, organizational support, employee performance and organizational performance, (2) The influence of competence on employee performance, (3) The influence of work ethic on employee performance, (4) The influence of organizational support on employee performance, (5) The influence of competence on organizational performance, (6) The influence of work ethic on organizational performance, (7) Effect of organizational support on organizational performance, (8) The influence of employee performance on organizational performance, (9) indirect influence of competence on organizational performance, (10) the indirect influence of work ethic on organizational performance and (11) Indirect influence of organizational support, on organizational performance. The object of this research is competence, work ethic, organizational support, employee performance and organizational performance. Data analysis equipment used in this research is descriptive test that is to test the descriptive statistic model based on mean value and verfikatif test by using data structural equation modeling (SEM) with Amos program. The results showed that the competence, work ethic, organizational support, employee performance and organizational performance, competence have an effect on to employee performance, work ethos influence to employee performance, organizational support influence to employee performance, competence influence to organizational performance, work ethic in that office also give influence to organizational performance, organizational support given also influential to organizational performance, employee employee performance have positive and significant effect to organizational performance, there is indirect influence of competence, work ethic and organizational support to organizational performance